The Black Sea near-past wave climate and its variability: a hindcast study - Causio, Salvatore; Federico, Ivan; Jansen, Eric; Mentaschi, Lorenzo; Ciliberti, Stefania Angela; Coppini, Giovanni; Lionello, Piero (Frontiers in Marine Science, 2024)
This study analyzed the past wave climate of the Black Sea region for the period from 1988 to 2021. The wave field has been simulated using the state-of-the-art, third-generation wave model WAVEWATCH III forced by the ECMWF reanalysis ERA5 winds, with the model resolution being the highest ever applied to the region in a basin-scale climate study. The surface currents provided by the Copernicus Marine Service have been included in the wave model to evaluate wave–current interactions. The wave model results have been validated with respect to satellite and buoy observations, showing that the simulation accurately reproduces the past evolution of the wave field, exceeding 0.9 correlation with respect to satellite data. The inclusion of wave–current interaction has been positively evaluated. Four statistics (significant wave height 5th and 95th percentiles, mean, and maxima) have been used to describe the wave field at seasonal timescale, showing a clear distinction between the Western (rougher sea conditions) and Eastern (calmer sea conditions) sub-basins. Furthermore, the intra-annual wave climate variability has been investigated using a Principal Component Analysis (PCA) and the Mann–Kendall test on significant wave height (SWH). This study represents the first time the PCA is applied to the region, identifying two main modes that highlight distinct features and seasonal trends in the Western and Eastern sub-basins. Throughout most seasons, the SWH trend is positive for the Eastern basin and negative for the Western basin. The PCA shows a regime shift with increasing eastward waves and decreasing north and north-eastward waves. Finally, SWH correlation (ρ) with four Teleconnection indexes (East Atlantic Pattern, Scandinavian Pattern, North Atlantic Oscillation, and East Atlantic/West Russia Pattern) revealed that the strongest ρ is observed with the Eastern–Atlantic–Western Russia teleconnection, with a peculiar spatial pattern of correlation, and is positive for the northwestern and negative for the southeastern sub-basin.